PERBANDINGAN UJI T STATISTIK RATA-RATA TERBOBOT DENGAN RATA-RATA TIDAK TERBOBOT PADA DATA KEUANGAN: (Studi Kasus Yield Obligasi Muncipal dan Korporasi Amerika Serikat dengan Rating AAA - , INDAH MENTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Means is technic to explanation the group or size in center set of data. Usually, a common statistical question arises when two random samples are taken from two different normal populations, possibly with different variances, and wish to know whether or not the means of the two populations are equal. To examine the similarity of the average, typically use t-test mean two samples. In this minithesis will describe about expansion of t-test mean two samples using tstatistic weighted means. This methode present a generalization of the two-sample t-test for equality of the means to the case where the sample values are to be given unequal weights. This is a natural situation in financial return modelling where some samples are considered more reliable than others in predicting a common mean. In this case show with an example of yield data that using the standard unweighted t-test can lead to the wrong statistical conclusion.